Lower bounds on the Erdős–Gyárfás problem via color energy graphs - Balogh, József; English, Sean; Heath, Emily; Krueger, Robert A. (Journal of graph theory, 2023)
Given positive integers p $p$ and q $q$, a ( p , q ) $(p,q)$‐coloring of the complete graph K n ${K}_{n}$ is an edge‐coloring in which every p $p$‐clique receives at least q $q$ colors. Erdős and Shelah posed the question of determining f ( n , p , q ) $f(n,p,q)$, the minimum number of colors needed for a ( p , q ) $(p,q)$‐coloring of K n ${K}_{n}$. In this paper, we expand on the color energy technique introduced by Pohoata and Sheffer to prove new lower bounds on this function, making explicit the connection between bounds on extremal numbers and f ( n , p , q ) $f(n,p,q)$. Using results on the extremal numbers of subdivided complete graphs, theta graphs, and subdivided complete bipartite graphs, we generalize results of Fish, Pohoata, and Sheffer, giving the first nontrivial lower bounds on f ( n , p , q ) $f(n,p,q)$ for some pairs ( p , q ) $(p,q)$ and improving previous lower bounds for other pairs.